KONSEP PENGAMPUNAN DOSA DALAM KRISTEN KATOLIK - Abu Bakar (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2011)
This article does analisis beneficial owner sin concept is design, about dalan's aught penance Catholic teachin. How most verily understanding one at catches by jemaat christian about that abolition. Penance constitutes keimanan's subject false in Christian Catholic, one that started by Jesus &n crufixion at cross by men that hats Jesus. This Constitutes one of effect punishment of fault outgrow that is done on its term. So rumawi Pontinus Pilatus's Governor sentences it by crucifies it at Cross